2015
DOI: 10.4049/jimmunol.1501138
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Contributes to the Pathogenesis of Endometriosis by Triggering Proinflammatory Cytokines and Angiogenic Growth Factors

Abstract: Endometriosis is a chronic, inflammatory disease characterized by the growth of endometrial tissue in aberrant locations outside the uterus. Neo-angiogenesis or establishment of new blood supply is one of the fundamental requirements of endometriotic lesion survival in the peritoneal cavity. IL-17A is emerging as a potent angiogenic and pro-inflammatory cytokine involved in the pathophysiology of several chronic inflammatory diseases such as rheumatoid arthritis and psoriasis. However, sparse information is av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 41 publications
7
127
2
4
Order By: Relevance
“…Regarding IL-17A, a very recent study showed differential expression of IL-17A in human ectopic endometriotic lesions and matched eutopic endometrium from women with endometriosis. Moreover, surgical removal of lesions resulted in significantly reduced plasma IL-17A concentrations, thus showing that endometriotic lesions produce IL-17A and that the removal of the lesion via laparoscopic surgery leads to a significant reduction in systemic levels of IL-17A (28). Our results show similar levels between endometriosis patients and controls, thus adding to the controversy around the role of IL-17A in the context of endometriosis.…”
Section: Discussionsupporting
confidence: 69%
“…Regarding IL-17A, a very recent study showed differential expression of IL-17A in human ectopic endometriotic lesions and matched eutopic endometrium from women with endometriosis. Moreover, surgical removal of lesions resulted in significantly reduced plasma IL-17A concentrations, thus showing that endometriotic lesions produce IL-17A and that the removal of the lesion via laparoscopic surgery leads to a significant reduction in systemic levels of IL-17A (28). Our results show similar levels between endometriosis patients and controls, thus adding to the controversy around the role of IL-17A in the context of endometriosis.…”
Section: Discussionsupporting
confidence: 69%
“…Endometrial cells have been shown to produce IL-8 and to have increased expression of IL-8 and cyclooxygenase (COX) 2 under stimulation of IL-17 in vitro (28), meaning they can stimulate local blood vessel formation. Our group recently confirmed that IL-17A is expressed in the eutopic and ectopic endometrium of women with endometriosis, and that IL-17A stimulation of cultured endometrial cells induces the production of VEGF, G-CSF, PDGF-AA, and stromal cell–derived factor 1 (23), which could be a mechanism by which ectopic lesions increase IL-8 production.…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, ectopic tissue was found to express higher levels of GM-CSF than eutopic tissue, further indicating that ectopic lesions are driving the aberrant expression of this cytokine. Meanwhile, IL-8 is a chemotactic and angiogenic factor previously shown to contribute to neutrophil recruitment and blood vessel formation in endometriotic lesions (23, 24). High levels of IL-8 have previously been detected in the PF and serum of women with endometriosis (25, 26), which supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation assay was performed as previously described52. Briefly, PAOEC and PTr2 cells were cultured at the rate of 1.25 × 10 4 cells/well in two separate 96 well plates for 24 hrs.…”
Section: Methodsmentioning
confidence: 99%